2021
DOI: 10.1186/s40478-021-01147-0
|View full text |Cite
|
Sign up to set email alerts
|

Tau antibody isotype induces differential effects following passive immunisation of tau transgenic mice

Abstract: One of the main pathological hallmarks of Alzheimer’s disease (AD) is the intraneuronal accumulation of hyperphosphorylated tau. Passive immunotherapy is a promising strategy for the treatment of AD and there are currently a number of tau-specific monoclonal antibodies in clinical trials. A proposed mechanism of action is to engage and clear extracellular, pathogenic forms of tau. This process has been shown in vitro to be facilitated by microglial phagocytosis through interactions between the antibody-tau com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…This suggests the dose of RNF5 delivered into the brain may have been too high and that the benefit of SUS +MB might have reached a threshold in that attempting to deliver too much antibody into the brain may then become toxic. This is especially the case because RNF5 is of a murine IgG2b isotype, and it is important to note that high concentrations of a high effector isotype antibody may ultimately be deleterious, as we have demonstrated previously [40]. By further exploring the possibility of toxicity, on top of observing acute neuronal degeneration, we also found that microglia had infiltrated the areas in the brain parenchyma into which RNF5 had extravasated.…”
Section: Discussionsupporting
confidence: 62%
“…This suggests the dose of RNF5 delivered into the brain may have been too high and that the benefit of SUS +MB might have reached a threshold in that attempting to deliver too much antibody into the brain may then become toxic. This is especially the case because RNF5 is of a murine IgG2b isotype, and it is important to note that high concentrations of a high effector isotype antibody may ultimately be deleterious, as we have demonstrated previously [40]. By further exploring the possibility of toxicity, on top of observing acute neuronal degeneration, we also found that microglia had infiltrated the areas in the brain parenchyma into which RNF5 had extravasated.…”
Section: Discussionsupporting
confidence: 62%
“…In a third study, Bajracharya et al examined the efficacy of the tau antibody RN2N in isolated mouse microglia and in a mouse tauopathy model. 31 As expected, the mouse IgG2A (full effector function, comparable to human IgG1) promoted glial phagocytosis of tau more effectively in culture than the mouse IgG1 (less effector function). However, the two subclasses had a similar effect in the mice on clearing several soluble and insoluble phospho-tau epitopes as quantified on western blots, although the IgG1 subclass appeared to be more effective in clearing a particular phospho-tau epitope on immunostained brain sections.…”
Section: Introductionsupporting
confidence: 61%
“…We have previously shown that adding PHF and antibody together to cultures results in complexes of the two, 33 and other groups have shown that antibody bound tau can be cleared via microglia in an Fc-dependent manner. 19 , 20 , 31 , 54 , 55 , 56 , 57 Because phagocytosis of exogenous tau requires Fc receptor binding, it is also likely to be impacted by subclass.…”
Section: Resultsmentioning
confidence: 99%
“…Tau seeds immunodepleted by C10.2 are less competent at inducing tau aggregation and spread in cellular assays and in rTg4510 tau transgenic mice [ 85 ]. Specifically, the C10.2 antibody has been demonstrated to help mediate lysosomal degradation of pathogenic tau by microglia in cell culture experiments [ 181 ], and in general, antibody uptake is dependent on its isotype and other characteristics [ 193 ]. This antibody has been humanized as Lu AF87908 by H. Lundbeck company and will be tested in a Phase I clinical trial, which is expected to be completed in May of 2021 [ 194 ].…”
Section: Main Textmentioning
confidence: 99%